Sistem Informasi Administrasi Forum Kesehatan Kelurahan (FKK) Berbasis Web Kelurahan Wonoplumbon - Yunus Yunus Anis; Eko Nur Wahyudi; Purwatiningtyas; Cici Suhartini (Bulletin of Information Technology (BIT), 2022)
FKK is a form of community participation in planning, determining, and moving activities as well as monitoring in evaluating health processes at the village level. The activity of FKK has become a success for an Active Alert Village. The FKK consists of the Lurah, puskesmas, community leaders, and health cadres. The FKK can make various activities in the community run in the health sector, both in cooperation, health protection, monitoring and observation, as well as providing joint costs. The FKK also implements arrangements according to the potential of their respective regions. This arrangement is carried out in the form of activities, interventions from problems that exist in the region itself. It can be seen from the many arrangements and activities of the FKK that require a lot of administrative data and information so that a system is needed that can help work related to the administration of the FKK. From the beginning, which is still managed manually, in this research, a web-based system will be developed that can help manage administrative data in Wonoplumbon village. By using the waterfall method and the PHP programming language, CSS and Bootstrap Framework, as well as database processing using MySQL, it is hoped that this system can run well on the website. Through the method used, the system will be built following the sequence of processes from analysis, design, implementation, system testing to maintenance